Factors related to the appearance and development of burnout in nursing students: a systematic review and meta-analysis - Velando-Soriano, Almudena; Suleiman-Martos, Nora; Pradas-Hernández, Laura; Membrive-Jiménez, María José; Ramírez-Baena, Lucia; Gómez-Urquiza, Jose L.; Cañadas-De La Fuente, Guillermo Arturo (Frontiers in Public Health, 2023)
Introduction: burnout may be suffered not only by experienced nurses, but also by those in training. The university environment can be highly stressful for student nurses, who are exposed to various stress-producing situations. Aim: the aim of this study is to identify and analyse the main risk factors for burnout among nursing students. Methods: a systematic review with meta-analysis was performed. The search equation used was “Burnout AND Nursing students”. Quantitative primary studies on burnout in nursing students, and related risk factors published in English or Spanish and with no restriction by year of publication were included. Results: A sample of n=33 studies were included. Three variables are identified can influence burnout in nursing students: academic, interpersonal, environmental and/or social factors. The meta-analyses, with the higher sample of n=418 nursing students, show that some personality factors, empathy, and resilience are correlated with emotional exhaustion, depersonalization and personal accomplishment. Conclusion: the factors that can influence the development of burnout in nursing students, such as resilience, personality factors, and empathy, among others, must be taken into account when preventing the appearance and treating burnout.